2017
DOI: 10.14393/bj-v33n4a2017-34319
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry of the epididymal region of domestic quail (Coturnix coturnix) of the italian variety

Abstract: Epididymal region of domestic adult quail of the italina variety was studied by morphometric analysis concerning to the proximal and distal efferent ductules and the epididymal duct. They formed the proper segmental epididymal region structure in domestic quail prior observed during the four seasons of the year in the Botucatu city/SP/Brazil (22°53'09''S, 48°26'42''W, 840m), with tropical altitude climate, average annual temperature of 20,7 degrees. Parameters such as the tubular diameter and the luminal diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A previous study in fowl, duck, and domestic/feral guinea fowl by Aire (2002b) indicated age‐related morphological changes including a poorly developed subapical tubulovacuolar system in the nonciliated Type I cells of the proximal efferent duct during prepubertal development when compared to mature, sexually active birds. Furthermore, a reduction in the epithelial height and luminal diameter was also reported in the epididymal duct of quail (Orsi et al, 2017) and fowl (Abdul‐Rahman et al, 2016) during the nonbreeding season. Abdul‐Rahman and Jeffcoate (2018) reported age‐related morphological changes in male guinea fowl, that is, an increase in the tubular diameter in all excurrent ducts of the testis with age.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…A previous study in fowl, duck, and domestic/feral guinea fowl by Aire (2002b) indicated age‐related morphological changes including a poorly developed subapical tubulovacuolar system in the nonciliated Type I cells of the proximal efferent duct during prepubertal development when compared to mature, sexually active birds. Furthermore, a reduction in the epithelial height and luminal diameter was also reported in the epididymal duct of quail (Orsi et al, 2017) and fowl (Abdul‐Rahman et al, 2016) during the nonbreeding season. Abdul‐Rahman and Jeffcoate (2018) reported age‐related morphological changes in male guinea fowl, that is, an increase in the tubular diameter in all excurrent ducts of the testis with age.…”
Section: Introductionmentioning
confidence: 65%
“…In the current study, there was also an increase in the epithelial heights, luminal and tubular diameters, as well as the cross-sectional areas of all ducts of the epididymal duct unit with age. Reduction of the epithelial height and the luminal diameter in the epididymal duct has been reported in domesticated quail (Orsi et al, 2017) and guinea fowl (Abdul-Rahman et al, 2016), during the nonbreeding season. In addition, Aire (2002a) indicated epithelial atrophy and reduction in luminal diameters of the connecting duct and epididymal duct of sexually mature, but inactive or resting domestic fowl and duck compared with those of sexually mature and active.…”
Section: Epididymal Duct Unitmentioning
confidence: 93%
See 1 more Smart Citation